Ocorrência de afídeos em alface (lactuca sativa L.) em cultivo hidropônico - Auad, Alexander M. [UNESP]; De Freitas, Sérgio [UNESP]; Barbosa, Leonardo R. [UNESP] (My University, 2002)
The occurrence of aphids was evaluated on lettuce hydroponically grown at the Escola Agrotécnica of the State University of São Paulo (UNESP) located in Jaboticabal County, State of São Paulo, Brazil, from January to December 1999. The total number of each species of aphids present in weekly samplings performed during the period was found to be correlated with the average temperature recorded within the respective sampling period. The occurrence of three species, Uroleucon ambrosie (Thomas), Myzus persicae (Sulzer) and Macrosiphum euphorbiae (Thomas) was recorded, with the highest population densities being coincident with mean temperatures below 21.5°C. The highest population densities of U. ambrosie occurred from May to June. In the second week of May and third week of November, two maximum population peaks were recorded for M. persicae. The species M. euphorbiae was predominant over the others and the highest populations of this species were observed from May to June and from late July to early September. A negative correlation was found between populations of aphids and temperature. This correlation, however, was statistically significant only for M. euphorbiae and U. ambrosiae.
Occurrence of aphids on lettuce (lactuca sativa L.) under hydroponic cultivation
Keywords: Aphididae; Insecta; Macrosiphum euphorbiae; Myzus persicae; Uroleucon ambrosiae